Influence of root exudate carbon compounds of three rice genotypes on rhizosphere and endophytic diazotrophs - Naher, Umme Aminun; Othman, Radziah; Mohd Saud, Halimi; Shamsuddin, Zulkifli; Ismail, Mohd Razi (Universiti Putra Malaysia Press, 2009)
Root exudates play an important role in microbial colonization of the rhizosphere. An in vitro experiment was conducted to study the root exudate sugars and production of amino acids of three different rice (Oryza sativa) genotypes, as well as the influence of these compounds on Rhizobium sp. (Sb 16) and Corynebacterium sp. (Sb26) colonization. Using HPLC, a total of 7 carbohydrate sugars and 16 amino acids were identified from the Mahsuri, Mayang Segumpal and MR219 rice root exudates. A significant (p<0.05) relationship was observed between diazotrophic population growth and root exudates sugar and amino acid consumption of the three rice varieties. Higher bacterial population was found in the plant rhizosphere, as compared to the endosphere. Rhizobium sp. consumed more sugar and produced higher rhizosphere population as compared to Corynebacterium sp. The Rhizobium sp. consumed 100% of mannose, xylose, arabinose and sucrose in the root exudates of three rice genotypes. The differences in sugar consumption by Corynebacterium sp. were observed between the rice varieties. Corynebacterium sp. consumed 100% mannose, xylose and fructose in Mahsuri rice, 100% xylose and arabinose in Mayang Segumpal and 100% arabinose and sucrose in MR219 variety. The identification of the preferred carbon sources by the diazotrophs and the selection of genotypes which produce these compounds may increase the root colonization and subsequently N fixation in the rice plants.